2020
DOI: 10.3390/su12166336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zeolite and Biochar Addition on Ammonia-Oxidizing Bacteria and Ammonia-Oxidizing Archaea Communities during Agricultural Waste Composting

Abstract: The effects of zeolite and biochar addition on ammonia-oxidizing bacteria (AOB) and archaea (AOA) communities during agricultural waste composting were determined in this study. Four treatments were conducted as follows: Treatment A as the control with no additive, Treatment B with 5% of zeolite, Treatment C with 5% of biochar, and Treatment D with 5% of zeolite and 5% biochar, respectively. The AOB and AOA amoA gene abundance as well as the ammonia monooxygenase (AMO) activity were estimated by quantitative P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Our previous research suggested that the fungal community might be more sensitive to moisture regulation than the bacterial counterparts [55]. Further studies are needed to determine the ecology and functions of microorganisms related to nitrogen transformation when biochar/zeolite is added during the agricultural waste composting process [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research suggested that the fungal community might be more sensitive to moisture regulation than the bacterial counterparts [55]. Further studies are needed to determine the ecology and functions of microorganisms related to nitrogen transformation when biochar/zeolite is added during the agricultural waste composting process [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al [12] conducted a study related to predicting the compost's maturity from fermented agricultural waste through the dynamic trough composting method. Besides, Wu et al [13] have also tested the addition of Zeolite and Biochar during composting of agricultural waste. Besides, Phibunwatthanawong and Riddech [11] has also conducted research to produce liquid organic fertilizers for hydroponic cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…AMO is a key enzyme that catalyses the first step of the ammonium oxidation process and mainly affects the NH 4 + ‐N conversion to NH 2 OH (Wu et al, 2020). The activity of AMO is lower in the treatment with NO 3 − ‐based fertilizer, and it is interesting to note that the combination of BC and N fertilizer caused a decreasing trend in AMO rather than the addition of N alone (Figure 2).…”
Section: Discussionmentioning
confidence: 99%